Rediscovering the importance of oils in medication: translation of the section on oils in Kitab Al-Aghdhiyyah of Ibn Zuhr (D.1162 C.E.) - Medikawati, Mersita Eko; El-Nagar, Hassan Abdelraziq (2010)
The development of medical science had been the fruit of a conscious attempt to solve the problem medical and health care of the Muslim community. Based upon principles that are derived from the basic teachings of the religion of Islam, this branch of knowledge is always in conformity with the Islamic worldview in which God, man and the nature are closely intertwined. However, Islamic medicine has been considered irrelevant to the needs of a modern society. The firm conviction that the Islamic medical system would be the most suitable system for the Islamic way of life calls the need to rediscover and revive the philosophy of Islamic medicine. Kitab Al-Aghdhiyyah, one of the classic texts that had ever been written in the field of medicine, can be one of the source to develop the philosophy of Islamic medicine. The text was written by one of the greatest Moslem doctors in the 12th century, Abu Marwan Abd Al-malik Ibn Zuhr(d.1162). The author came from a family in Seville whose family members were famous doctors in their era. Ibn Zuhr, who served Almmohad dynasty wrote at least six books on medical science; this text is one of three books that had been survived out of six. Estimated to be written between 1130C.E., this text has not been studied a lot. It cover vast variety of topics in medicine, including types of oils that are useful in medication besides various diets, condiments, culinary preparations, drinks, medicaments and rules of hygiene. Over 23 kinds of oil extracted from seeds and flowers are mentioned in the text together with the way they are used in curing diseases. This paper would describe them and is expected to be the preliminary stage to the further researches.